Pengaruh Transparansi, Kompetensi, Dan Sistem Akuntansi Keuangan Terhadap Akuntabilitas Pengelolaan Keuangan Daerah Dengan Penerapan Sistem Pengendalian Internal Pemerintah Sebagai Variabel Moderasi - Ria Herlina; Taufeni Taufik; Azwir Nasir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to examine the effect of transparency, competency, financial accounting systems on the accountability of regional financial management with the government's internal control system as a moderating variable with a case study in Indragiri Hulu Regency. The population of this study were all employees in all OPDs in Indragiri Hulu Regency as many as 45 OPDs so that a sample of 180 respondents was obtained from this population using the purposive sampling method. The data analysis method used in this research is the quantitative analysis method with WarpPLS version 6.0 as data processing software. The results show that transparency, competency, and financial accounting systems affect the accountability of regional financial management, the implementation of the government internal control system can moderate the effect of transparency and financial accounting systems on the accountability of regional financial management, and the implementation of the government internal control system cannot moderate the effect of competency on the accountability of regional finance management. Keywords: Transparency, Competency, Financial Accounting System, The Accountability of Regional Financial Management, Implementation of The Government Internal Control System